Recombinant activated factor VII in clinical practice: a 2014 update - Franchini, Massimo; Crestani, Silvia; Frattini, Francesco; Sissa, Cinzia; Bonfanti, Carlo (Journal of thrombosis and thrombolysis, 2015)
Recombinant activated factor VII (rFVIIa) was initially developed to treat bleeding episodes in patients with congenital hemophilia and inhibitors. Due to the initial success in this clinical setting, its use has been extended to other coagulopathies characterized by impaired thrombin generation, i.e. acquired hemophilia, inherited factor VII deficiency and Glanzmann’s thrombasthenia, for which it is currently licensed. Extensive research in the last decade has increased our knowledge of the mechanisms utilized by rFVIIa to restore normal hemostasis. This paper reviews current understanding of the mechanisms of action of rFVIIa before summarizing the clinical experience, in terms of safety and efficacy, to date in its licensed indications.